Dutch Influence to the Lifestyle of the Priyai Kraton Kasunanan Surakarta During the Reign of Sunan Pakubuwana X Year 1893-1915 - Asmarina, Maya; Afwan, Bahtiar (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The purpose of this study was to knew the Dutch influence to the lifestyle of the priyai Kraton Kasunanan Surakarta during the reign of Sunan Pakubuwana X Year 1893-1915. The study was using history method with qualitative analysis technique. The data in this research were collected by literature study. The result of study showed that there are materials aspect of the lifestyle of the priyai Kraton Kasunanan Surakarta during the reign of Sunan Pakubuwana X Year 1893-1915 that got Dutch influenced, that was fashion style, food menu and cutlery, entertainment and residential building.The conclusion of this study is Dutch as a culture figure was brought change in material aspects of the the lifestyle of the priyai Kraton Kasunanan Surakarta during the reign of Sunan Pakubuwana X Year 1893-1915